2018
DOI: 10.1007/s11596-018-1846-9
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Helios Expression in Tregs from Patients with Hypertension

Abstract: Regulatory T cells (Tregs) play a pivotal role in the pathological development of hypertension. Helios, a transcription factor from the Ikaros family, was recently reported to be a bona fide marker for natural Tregs or activated Tregs with suppression function, however, little has been known about its role in hypertension. This study was aimed to find whether Helios+ Tregs really play a vital role in hypertension. A total of 60 hypertension patients, and 46 normotension subjects were enrolled in this study. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Higher susceptibility of CD31 + Treg to apoptosis could partially explain the lower atheroprotective functions of Tregs in CAD + PWH in our study. In addition, lower expression of FoxP3 and Helios is also observed in patients with hypertension [45]. Our data showing an increase in both recent thymic emigrants and thymic Tregs in PWH with CAD suggests that HIV infection contributes to a higher thymic output of these cells.…”
Section: Discussionsupporting
confidence: 55%
“…Higher susceptibility of CD31 + Treg to apoptosis could partially explain the lower atheroprotective functions of Tregs in CAD + PWH in our study. In addition, lower expression of FoxP3 and Helios is also observed in patients with hypertension [45]. Our data showing an increase in both recent thymic emigrants and thymic Tregs in PWH with CAD suggests that HIV infection contributes to a higher thymic output of these cells.…”
Section: Discussionsupporting
confidence: 55%
“…Decreased levels of Helios+ Tregs have been observed in patients with hypertension and rheumatoid arthritis, with lower expression levels correlating with increased inflammatory markers 84 . Tregs may protect against hypertension by limiting vascular inflammation through suppression of effector T cells 85,86 . Furthermore, our analysis revealed that variants in IZKF2 were disproportionately co-associated with patients with hypertension ( Figure 10).…”
Section: Vascular Inflammation Autophagy and Cardiovascular Dysfunctionmentioning
confidence: 99%
“…Extensive studies evaluating human Tregs in the context of hypertension are yet to be undertaken. Only one study published in 2018 exists, in which authors reported the down-regulation of Helios + Tregs in hypertensive patients as compared to their normotensive counterparts (60). Additionally, CD4 + T-cells from hypertensive patients have lower FOXP3 mRNA levels than cells from healthy controls (60).…”
Section: The Bidirectional Relationship Between Tregs and Risk Factorsmentioning
confidence: 99%
“…Only one study published in 2018 exists, in which authors reported the down-regulation of Helios + Tregs in hypertensive patients as compared to their normotensive counterparts (60). Additionally, CD4 + T-cells from hypertensive patients have lower FOXP3 mRNA levels than cells from healthy controls (60). This data might suggest that the hypertensive microenvironment can negatively impact Tregs populations.…”
Section: The Bidirectional Relationship Between Tregs and Risk Factorsmentioning
confidence: 99%